Frente o lápis e o papel: uma discussão sobre a instituição da posição leitor - Costa, Fabiana Regiani da (2012)
This study raise questions and discusses issues related to relationship child - text particularly, problems that arise during the process concerning the learning of writing and reading. Some children face special difficulties which may block the above mentioned process, i.e, they may delay and/or fail in establishing an effective and productive relation with writing and reading. Those students are usually sent to the speech-therapy clinic because their production is considered pathological. This study starts from and focus the difficult paths some children experience in reading and endeavors to contribute to the understanding of the intriguing aspects that lead to school failure and that shed light on successful outcomes. Those children become fixed in an awkward position face-to-face written texts they do not achieve the expected condition of a reader". The discussion was guided by some questions: What is the connection between the act of writing and that of reading? Could it be said that a child writes but does not read - or that s/he reads but does not write? This study also raises some clinical questions and discusses the decisive value of the diagnostic (language evaluation) as the very means to block the tendency to approximate in a naïve way educational evaluation and the clinical one. The theoretical basis that guides the discussion and analysis here presented is that developed in the CNPq Research Group: Acquisition, pathology and language clinic, which was established and supervised by Maria Francisca Lier-DeVitto at LAELPUCSP. This trend of investigation is also developed at Derdic-PUCSP, by researchers from the same Group. The theoretical trend known as Interactionism in Language Acquisition (De Lemos - 1992), the European Structuralism in Linguistics and Psychoanalysis stand as fundamental theoretical realms